Cascade Fluorescent Sensors Based on Isothermal Signal Amplification for the Detection of Mercury and Silver Ions - Zhen Liu; Xing Liu; Jie Sun; Xilin Xiao (Biosensors)
In this study, novel fluorescent DNA biosensors for mercury (Hg2+) and silver (Ag+) ions were developed based on thymine (T)- and cytosine (C)-rich recognition elements in combination with exonuclease III and a mismatch-catalyzed hairpin assembly (MCHA)-based cascade isothermal signal-amplification strategy. In the presence of the respective target analytes, the recognition element terminals form so-called T-Hg2+-T or C-Ag+-C structures, resulting in cleavage by Exo III and the release of the trigger strand for MCHA. This binds to the H1 hairpin, which is fluorescently labeled with carboxyfluorescein (FAM) and tetramethylrhodamine (TAMRA), disrupting fluorescence resonance energy transfer between them and, thus, restoring FAM fluorescence, generating a strong signal at 520 nm. The linear range of the Hg2+ sensor is 0.5 to 3 pM, with a detection limit of 0.07 pM. The recovery range in actual spiked water samples is between 98.5% and 105.2%, with a relative standard deviation (RSD) ranging from 2.0% to 4.2%. The linear range of the Ag+ sensor is 10 to 90 pM, with a detection limit of 7.6 pM. The recovery range in actual spiked water samples is between 96.2% and 104.1%, with an RSD ranging from 3.2% to 6.3%. The cascade isothermal signal amplification strategy effectively enhances sensor sensitivity, while MCHA decreases the false-positive rate. The aptamer sensor exhibits high specificity, is resistant to interference, and can be used for the detection of Hg2+ and Ag+ in environmental water samples.